(untitled) (Fiep Bulletin - online, 2019)
This paper aims to evaluate the deaf professors Quality of Life (QoL) in a public institution. Regarding the data collectprocedure, the WHOQOL -bref instrument of quality of life assessment was used, composed by 26 questions, within two aregeneral quality of life questions and 24 represent facets. The results show that the facets with the highest scores were“Spirituality/religion/personal beliefs” with 83,33 and “Home Environment” with 80,56. The facets with the lowest scores were“Physical environment” with 52,78, “Financial resources” with 58,33 and “Thinking/learning/memory/concentration”, also with58.33. The domain with the highest score was "Social relationships" with 73,15, being one of the hypothesis the last-years increase of the Knowledge and access to Brazilian Sign Language. Whereas the domain with the lowest score was“Environment" with 68.75. These professors need academic community support, who knows inclusion, to increase thecommunication between listeners and deaf people is concluded.